Transport study on as-grown and cast films of electrogenerated poly(3-hexylthiophene) - Jiang, Xiaoqing; Harima, Yutaka; Patil, Rahul (Materials Letter, 2007)
Two kinds of poly(3-hexylthiophene) films with identical chemical compositions are prepared. One of the films is obtained by electropolymerization of 3-hexylthiophene (as-grown film) and the other is prepared by casting a solution dissolving the as-grown film (cast film). A clear difference is found in the mobility vs. doping level plots between the as-grown and cast films and its reason is discussed. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: mobility; poly(3-hexylthiophene); swelling; thin film; transport mechanism